Positive lithium supplementing material and preparation method thereof, positive pole piece, battery and power utilization device

By applying the coating modification of the fast ion conductor and electronic conductor of LixMyOz, the problem of poor chemical stability of the positive electrode lithium supplement material is solved, and the first charging and discharging efficiency of lithium-ion batteries is improved.

CN119517987APending Publication Date: 2025-02-25BYD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411551634.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement materials have problems such as poor chemical stability, which leads to a reduction in the first charge and discharge efficiency of lithium-ion batteries.

Method used

Fast ion conductors and electronic conductors are used to surface coat and modify LixMyOz to form a cladding layer to improve the interface stability, electron conduction and ion conduction capabilities of the material.

Benefits of technology

The interface stability and decomposition efficiency of the positive electrode lithium supplement material are improved, the rapid migration ability of lithium ions is improved, and the initial charging and discharging efficiency of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115950830000161
    Figure BDA0005115950830000161
  • Figure BDA0005115950830000171
    Figure BDA0005115950830000171
  • Figure BDA0005115950830000181
    Figure BDA0005115950830000181
Patent Text Reader

Abstract

The invention discloses a positive electrode lithium supplementing material and a preparation method thereof, a positive electrode plate, a battery and a power utilization device, the positive electrode lithium supplementing material comprises: an inner core, the inner core comprises a lithium supplementing agent, the lithium supplementing agent comprises LixMyOz; the coating layer coats at least part of the surface of the inner core, and the material of the coating layer comprises a fast ion conductor and an electronic conductor. The positive electrode lithium supplementing material is high in stability, high in decomposition efficiency, high in electron conduction and ion conduction capacity and good in lithium supplementing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically to positive electrode lithium supplement materials and preparation methods thereof, positive electrode plates, batteries and electrical devices. Background Art

[0002] During the initial charging process of lithium-ion batteries, a layer of film called solid electrolyte interface (SEI) is generated on the surface of the negative electrode material. This process consumes the active lithium ions in the positive electrode, resulting in a decrease in the initial charge and discharge efficiency of the battery. By introducing positive electrode lithium supplement materials to replenish the lithium ions lost in the first cycle, it helps to restore the lithium ion balance of the battery, thereby improving the initial charge and discharge efficiency of the battery. However, the current positive electrode lithium supplement materials have problems such as poor chemical stability. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a positive electrode lithium replenishing material and a preparation method thereof, a positive electrode sheet, a battery and an electric device. The positive electrode lithium replenishing material of the present application has strong stability, high decomposition efficiency, strong electronic conduction and ion conduction capabilities, and good lithium replenishing effect.

[0004] The first aspect of the present application proposes a positive electrode lithium replenishing material. According to an embodiment of the present application, the positive electrode lithium replenishing material includes:

[0005] The core includes a lithium supplement, and the lithium supplement includes Li x M y O z , M includes at least one of Fe, Co and Ni, 1≤x≤6, 1≤y≤6, 1≤z≤6;

[0006] A coating layer, wherein the coating layer covers at least a portion of the surface of the core, and the material of the coating layer includes a fast ion conductor and an electronic conductor;

[0007] The electronic conductor includes at least one of aluminum-doped zinc oxide (AZO), antimony-doped tin dioxide (ATO), indium tin oxide (ITO), aluminum nitride, titanium nitride, gallium nitride, niobium nitride and indium nitride.

[0008] According to the positive electrode lithium supplement material of the embodiment of the present application, the fast ion conductor and the electronic conductor are used to x M y O z Surface coating modification can not only improve Li x M y O z The interface stability can also reduce its reaction with H2O and CO2 in the air, thus improving the Li x M yO z Decomposition efficiency. The fast ion conductor itself has good ion conductivity. x M y O z The surface can provide more lithium ion transmission channels, thereby improving the ionic conductivity of the material. The electronic conductor material itself has good electronic conductivity. Introducing an electronic conductor into the positive electrode lithium supplement material can improve its electronic conduction ability. In addition, compared with using only one of them, the use of fast ion conductors and electronic conductors for co-coating can provide more grain boundaries, thereby increasing the lithium ion transmission path and promoting the rapid migration of lithium ions. This structure not only improves the interface reaction kinetics, but also helps to achieve a more uniform charge distribution and more efficient ion transmission, improve the decomposition efficiency of the positive electrode lithium supplement material, and enhance the lithium supplement effect. Among them, at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride, niobium nitride and indium nitride is used as an electronic conductor, and the positive electrode lithium supplement material formed has a better lithium supplement effect.

[0009] According to the embodiments of the present application, the above-mentioned positive electrode lithium supplement material may also have the following additional technical features:

[0010] According to an embodiment of the present application, the fast ion conductor includes: at least one of lithium aluminum titanium phosphate (LATP, solid electrolyte), lithium aluminum germanium phosphate (LAGP, solid electrolyte), lithium cobalt oxide (LiCoO2), lithium niobate (LiNbO3, solid electrolyte) and lithium nickel manganese oxide (also known as NCM ternary positive electrode material in the usual sense).

[0011] According to an embodiment of the present application, the fast ion conductor comprises: at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium cobalt oxide, and lithium niobate;

[0012] And / or, the electronic conductor includes at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride and indium nitride.

[0013] According to an embodiment of the present application, the D 50 The particle size is larger than the D 50 Particle size;

[0014] and / or, the electron conductor D 50 Particle size is 1nm~20nm;

[0015] and / or, the fast ion conductor has a D 50 The particle size is 50nm~200nm.

[0016] According to an embodiment of the present application, the D 50Particle size and the D of the electronic conductor 50 The particle size ratio is (2~100):1.

[0017] According to an embodiment of the present application, the Li x M y O z D 50 The particle size is larger than the D 50 Particle size.

[0018] According to an embodiment of the present application, the Li x M y O z D 50 The particle size is 1μm~20μm.

[0019] According to an embodiment of the present application, the lithium supplement includes Li5FeO4, Li6CoO4 or Li2NiO2.

[0020] According to an embodiment of the present application, the mass ratio of the core to the coating layer is 100:(0.1-10);

[0021] And / or, the mass ratio of the fast ion conductor to the electronic conductor is (50-99.9):(0.1-50).

[0022] The second aspect of the present application proposes a method for preparing the positive electrode lithium supplement material described in the first aspect of the present application. According to an embodiment of the present application, the method comprises:

[0023] The fast ion conductor and the electronic conductor are coated on at least a portion of the surface of the lithium supplement agent to form a coating layer, thereby obtaining the positive electrode lithium supplement material.

[0024] According to an embodiment of the present application, the method includes:

[0025] Mixing the fast ion conductor, the electronic conductor, the lithium supplement agent and the organic solvent to obtain a mixed solution;

[0026] The mixed solution is spray-dried to obtain a solid powder;

[0027] The solid powder is sintered to obtain the positive electrode lithium supplement material.

[0028] According to an embodiment of the present application, the mass ratio of the total mass of the fast ion conductor, the electronic conductor and the lithium supplement agent to the mass ratio of the organic solvent is 1:(0.8-1.2);

[0029] And / or, the spray drying process satisfies at least one of the following conditions:

[0030] The pressure is 0.2MPa~1MPa;

[0031] Inlet air temperature is 100℃~300℃;

[0032] The outlet temperature is 80℃~100℃;

[0033] Feed rate is 0.5L / h~2L / h;

[0034] And / or, the sintering treatment temperature is 200° C. to 400° C., and the time is 1 hour to 2 hours.

[0035] In a third aspect, the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode lithium replenishing material, and the positive electrode lithium replenishing material includes the positive electrode lithium replenishing material described in the first aspect of the present application or the positive electrode lithium replenishing material obtained by the method for preparing the positive electrode lithium replenishing material described in the second aspect of the present application.

[0036] According to an embodiment of the present application, the mass fraction of the positive electrode lithium supplement material in the positive electrode active material layer is 0.05% to 5%.

[0037] The fourth aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes the positive electrode sheet described in the third aspect of the present application.

[0038] The fifth aspect of the present application provides an electric device. According to an embodiment of the present application, the electric device includes the battery described in the fourth aspect of the present application.

[0039] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0041] Figure 1 A schematic diagram of the structure of a positive electrode lithium supplement material according to an embodiment of the present application is shown.

[0042] Reference numerals:

[0043] 10: positive electrode lithium supplement material; 100: core; 200: coating layer. DETAILED DESCRIPTION

[0044] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0045] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0046] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0047] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0048] At present, the commonly used positive electrode lithium supplement material Li x M y O z Taking Li5FeO4 as an example, it easily reacts with H2O and CO2 in the air, which not only reduces its electrochemical activity, but also generates residual alkali that causes gas production in the battery, posing a safety hazard.

[0049] In view of this, the present invention adopts fast ion conductor and electronic conductor to x M y O z Surface coating modification can not only improve its interface stability and decomposition efficiency, but also enhance its electronic and ion conduction capabilities, which helps to enhance the lithium supplementation effect.

[0050] To this end, the first aspect of the present application proposes a positive electrode lithium supplement material. According to the embodiments of the present application, see Figure 1 The positive electrode lithium supplement material 10 comprises: a core 100 and a coating layer 200, wherein the core 100 comprises a lithium supplement agent, and the lithium supplement agent comprises Li x M y O z , M includes at least one of Fe, Co and Ni, 1≤x≤6, 1≤y≤6, 1≤z≤6; the coating layer 200 covers at least a portion of the surface of the core 100, and the material of the coating layer 200 includes a fast ion conductor and an electronic conductor; the electronic conductor includes: at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride, niobium nitride and indium nitride.

[0051] In the positive electrode lithium supplement material of the present application, the fast ion conductor is coated on at least part of the surface of the core, which can serve as a protective layer to reduce its reaction with H2O and CO2 in the air, maintain its electrochemical activity, and improve its stability. During the battery charging and discharging process, the fast ion conductor coating helps to maintain the Li x M y O z The structural integrity of the core will crack when the lithium supplement is removed. The coating layer can effectively reduce the amount of electrolyte that penetrates into the core and reduce side reactions. In addition, the fast ion conductor itself has good ion conductivity. x M y O z The surface can provide more lithium ion transmission channels, thereby improving the ionic conductivity of the material.

[0052] The electronic conductor material itself has good electronic conductivity. Introducing an electronic conductor into the positive electrode lithium supplement material can improve its electronic conduction ability. Moreover, when the electronic conductor is combined with the fast ion conductor, a large number of interfaces will be formed in the fast ion conductor phase compared to using only one of them. Compared with the transmission of lithium ions through particles, the transmission efficiency of lithium ions from the interface is higher, that is, these interfaces can serve as channels for the rapid transmission of lithium ions, promote the diffusion of lithium ions in the electrode material, and further improve the lithium ion conduction ability of the positive electrode lithium supplement material. In addition, more interfaces also mean more contact points, which helps to improve the structural stability of the material and reduce the material rupture caused by volume changes during the charging and discharging process. At the same time, it can better protect the core material and reduce its contact with H2O and CO2 in the air, thereby reducing the possibility of reaction.

[0053] Specifically, the electronic conductor includes at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride, niobium nitride and indium nitride. The use of the above electronic conductors can better improve the interface stability of the core material, improve the decomposition efficiency of the core material, and improve the electronic and ion conduction capabilities, which helps to improve the lithium supplementation effect and thus improve the battery performance. Exemplarily, the electronic conductor does not include carbon materials.

[0054] According to an embodiment of the present application, the fast ion conductor includes at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium cobalt oxide, lithium niobate and lithium nickel manganese oxide. According to a specific embodiment of the present application, the fast ion conductor includes at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium cobalt oxide and lithium niobate. The above fast ion conductor has good ion conductivity and is coated on Li x M y O zThe surface can provide more lithium ion transmission channels, thereby improving the ion conductivity of the material. In addition, the above-mentioned fast ion conductor and the above-mentioned electronic conductor work together to better improve the interface stability of the core material, improve the decomposition efficiency of the core material, help improve the lithium replenishment effect, and thus improve the battery performance.

[0055] According to an embodiment of the present application, the electronic conductor includes: at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride and indium nitride. The above-mentioned electronic conductor material has good electronic conductivity and can improve its electronic conduction ability. The above-mentioned electronic conductor is combined with a fast ion conductor to better improve the interface stability of the core material, improve the decomposition efficiency of the core material, and also improve the electronic conduction and ion conduction capabilities, which helps to improve the lithium supplementation effect and thus improve the battery performance.

[0056] According to an embodiment of the present application, the D 50 The particle size is larger than the D 50 Particle size. Small particles of electronic conductors are distributed in large particles of fast ion conductors. Because small particles of electronic conductors have a larger specific surface area and more active sites, when the large and small particles of the two phases are mixed, the two-phase mixture has more grain boundaries than the single phase of the fast ion conductor alone, thereby increasing the lithium ion transmission path and promoting the rapid migration of lithium ions. This structure not only improves the kinetics of interfacial reactions, but also helps to achieve a more uniform charge distribution and more efficient ion transmission, thereby improving the decomposition efficiency of positive electrode lithium supplement materials. In addition, small particles of electronic conductors can better fill the gaps between large particles of fast ion conductors, enhance the mechanical stability of positive electrode lithium supplement materials, help resist volume changes during battery charging and discharging, reduce material breakage and pulverization, thereby improving the cycle stability of the battery, and better protect the core material, reduce the contact of the core material with H2O and CO2 in the air, thereby reducing the possibility of reaction and improving its decomposition efficiency.

[0057] In this application, the “D 50 "Particle size" refers to the particle size corresponding to the cumulative volume distribution percentage reaching 50% in the particle size distribution of particles, starting from the small particle size side. 50 The particle size determination method can refer to GB / T19077-2016 "Laser Diffraction Method for Particle Size Analysis" to conduct laser particle size testing on the material.

[0058] According to an embodiment of the present application, the D 50 Particle size and the D of the electronic conductor 50 The particle size ratio is (2-100): 1. For example, the D 50 Particle size and the D of the electronic conductor 50The particle size ratio is 2:1, 10:1, 20:1, 40:1, 50:1, 60:1, 80:1, 100:1, etc. This helps to further improve the interface stability of the positive electrode lithium supplement material, better improve its decomposition efficiency, and further improve the electronic conduction and ion conduction capabilities, which helps to improve the lithium supplement effect.

[0059] According to an embodiment of the present application, the D 50 The particle size is 1 nm to 20 nm. For example, the D 50 The particle size is 1nm, 3nm, 5nm, 8nm, 10nm, 13nm, 15nm, 17nm, 20nm, etc. D 50 The particle size meets the above conditions, which can not only effectively improve the electronic conductivity of the positive electrode lithium supplement material, but also because the particle size of the electronic conductor is small, it has a larger specific surface area, increases the contact interface with the fast ion conductor, promotes the rapid migration of lithium ions, and helps to improve the structural stability of the material, reduce the material rupture caused by volume change during the charge and discharge process, and better protect the core material, reduce its contact with H2O and CO2 in the air, thereby reducing the possibility of reaction and improving its decomposition efficiency. In addition, the electronic conductor with the above particle size is easier to disperse evenly during the mixing process, improving the consistency of the positive electrode lithium supplement material and the uniformity of battery performance.

[0060] According to an embodiment of the present application, the D 50 The particle size is 50nm to 200nm. For example, the D 50 The particle size is 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, etc. The particle size of the fast ion conductor meets the above conditions and can provide a better ion diffusion channel and a suitable specific surface area, which helps to accelerate the transmission rate of lithium ions, improve the interface contact with the electrode material, enhance the interface stability, and reduce the polarization during the charge and discharge process, thereby improving the electrochemical performance of the battery, including improving the charge and discharge efficiency, enhancing the cycle stability and extending the battery life. Moreover, the fast ion conductor with the above particle size also helps to form a more uniform electrode structure, reduce the agglomeration of the positive electrode lithium supplement material, and improve the mechanical strength and thermal stability of the battery. In addition, it is more conducive to the small particle electronic conductor to fill the gap between the fast ion conductors with the above particle size, enhance the mechanical stability of the positive electrode lithium supplement material, help to resist volume changes during the battery charge and discharge process, reduce the crushing and pulverization of the material, thereby improving the cycle stability of the battery, and at the same time can better protect the core material, reduce the contact of the core material with H2O and CO2 in the air, thereby reducing the possibility of reaction and improving its decomposition efficiency.

[0061] According to an embodiment of the present application, the Lix M y O z D 50 The particle size is larger than the D 50 Therefore, it can not only better play the role of lithium supplementation, but also help the fast ion conductor and electronic conductor to be more fully and evenly coated on Li during the coating modification process. x M y O z At least a portion of the surface of the substrate is coated with a fast ion conductor and an electronic conductor to form a coating layer.

[0062] According to an embodiment of the present application, the Li x M y O z D 50 The particle size is 1 μm to 20 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, and 20 μm. In this way, the lithium supplementation effect can be better exerted, and the fast ion conductor and the electronic conductor can be more fully and evenly coated on the Li in the coating modification process. x M y O z At least a portion of the surface of the substrate is coated with a fast ion conductor and an electronic conductor to form a coating layer.

[0063] According to an embodiment of the present application, the lithium supplement includes Li5FeO4, Li6CoO4 or Li2NiO2.

[0064] According to an embodiment of the present application, the mass ratio of the core 100 to the coating 200 is 100:(0.1-10). Exemplarily, the mass ratio of the core to the coating is 100:0.1, 100:1, 100:2, 100:4, 100:5, 100:6, 100:8, 10:1, etc. The mass ratio of the core to the coating satisfies the above conditions, which can better protect the core material, reduce its reaction with H2O and CO2 in the air, maintain its electrochemical activity, improve its interface stability, and improve the decomposition effect; it can also better play the role of improving the electron transmission capacity and ion transmission capacity of the coating, thereby improving the lithium ion conductivity and electronic conductivity of the positive electrode lithium supplement material, improving the charge and discharge efficiency, enhancing the cycle stability and extending the battery life.

[0065] According to an embodiment of the present application, the mass ratio of the fast ion conductor to the electronic conductor is (50-99.9): (0.1-50). Exemplarily, the mass ratio of the fast ion conductor to the electronic conductor is 99.9:50, 99.9:40, 99.9:30, 99.9:20, 99.9:10, 50:40, 50:50, 50:20, 50:10, 50:0.1, 70:0.1, 99.9:0.1, etc. The mass ratio of the fast ion conductor to the electronic conductor meets the above conditions, which can not only effectively reduce the contact between the core material and moisture and carbon dioxide in the air, reduce adverse reactions, thereby enhancing the stability of the interface, and improving the decomposition effect of the core material and the initial charge and discharge efficiency of the battery. Moreover, the electronic and ionic conductivity of the positive electrode lithium supplement material can be improved at the same time, thereby improving its electrochemical performance as a whole.

[0066] In some embodiments, the doping ratio of aluminum in aluminum-doped zinc oxide is 1% to 10%, specifically 2% in the following embodiments; the doping ratio of antimony in antimony-doped tin dioxide is 1% to 50%, specifically 28% in the following embodiments.

[0067] The second aspect of the present application proposes a method for preparing the positive electrode lithium replenishing material described in the first aspect of the present application. According to an embodiment of the present application, the method includes: coating at least part of the surface of the lithium replenishing agent with the fast ion conductor and the electronic conductor to form a coating layer to obtain the positive electrode lithium replenishing material. As a result, the positive electrode lithium replenishing material obtained by the method of the present application has strong stability, high decomposition efficiency, strong electronic conduction and ion conduction capabilities, which helps to improve the lithium replenishment effect.

[0068] According to an embodiment of the present application, the method includes:

[0069] The fast ion conductor, the electronic conductor, the lithium supplement agent and the organic solvent are mixed to obtain a mixed solution;

[0070] The mixed solution is spray-dried to obtain a solid powder;

[0071] The solid powder is sintered to obtain the positive electrode lithium supplement material.

[0072] By spray drying, the fast ion conductor and the electronic conductor can be evenly dispersed on at least a portion of the surface of the lithium supplement agent to form a uniform coating layer.

[0073] According to an embodiment of the present application, the mass ratio of the total mass of the fast ion conductor, the electronic conductor and the lithium replenisher to the mass of the organic solvent is 1:(0.8-1.2). This is conducive to uniform dispersion of the fast ion conductor, the electronic conductor and the lithium replenisher in the organic solvent, and can reduce the amount of organic solvent remaining in the positive electrode lithium replenisher material to affect the battery performance.

[0074] According to an embodiment of the present application, the spray drying process satisfies at least one of the following conditions:

[0075] The pressure is 0.2MPa to 1MPa, for example, 0.2MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.8MPa, 1MPa;

[0076] The inlet air temperature is 100°C to 300°C, for example, 100°C, 150°C, 200°C, 250°C, 300°C;

[0077] The outlet temperature is 80°C to 100°C, for example, 80°C, 85°C, 90°C, 95°C, or 100°C;

[0078] The feed rate is 0.5L / h~2L / h.

[0079] The spray drying process meets the above conditions and can form a uniform and compact coating layer that is not prone to agglomeration.

[0080] According to an embodiment of the present application, the sintering temperature is 200°C to 400°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, and the sintering time is 1h to 2h, for example, 1h, 1.2h, 1.4h, 1.5h, 1.6h, 1.8h, 2h. Thus, the coating layer is further made denser and the coating layer is more tightly combined with the core.

[0081] It should be noted that the characteristics and advantages described above for the positive electrode lithium replenishing material are also applicable to the method for preparing the positive electrode lithium replenishing material, and will not be repeated here.

[0082] The third aspect of the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode lithium replenishing material, and the positive electrode lithium replenishing material includes the positive electrode lithium replenishing material described in the first aspect of the present application or the positive electrode lithium replenishing material obtained by the method for preparing the positive electrode lithium replenishing material described in the second aspect of the present application. Therefore, the positive electrode plate has all the characteristics and advantages of the aforementioned positive electrode lithium replenishing material, which will not be repeated here.

[0083] According to an embodiment of the present application, the mass fraction of the positive electrode lithium supplement material in the positive electrode active material layer is 0.05% to 5%. Exemplarily, the mass fraction of the positive electrode lithium supplement material in the positive electrode active material layer is 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. The positive electrode active material layer contains an appropriate amount of lithium supplement, which can not only make up for the loss of active lithium ions during the battery charging and discharging process, but also will not cause too little positive electrode active material in the positive electrode active material layer due to too high content of lithium supplement, which will then lead to insufficient reversible lithium insertion vacancies in the positive electrode active material layer, resulting in too low energy density of the battery.

[0084] According to an embodiment of the present application, the positive electrode active material layer further includes a positive electrode active material.

[0085] Exemplarily, the positive electrode active material may adopt the positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, or a composite material of lithium iron manganese phosphate and carbon.

[0086] According to an embodiment of the present application, the positive electrode plate further includes a positive electrode current collector, and the positive electrode active material layer is disposed on at least one side of the positive electrode current collector.

[0087] According to an embodiment of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0088] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0090] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0091] The fourth aspect of the present application provides a battery. According to an embodiment of the present application, the battery includes the positive electrode sheet described in the third aspect. The battery of the present application has good power performance, rate performance and cycle performance.

[0092] According to an embodiment of the present application, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0093] According to an embodiment of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0094] According to an embodiment of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0095] According to an embodiment of the present application, the negative electrode active material may adopt a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0096] According to an embodiment of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0097] According to an embodiment of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0098] According to an embodiment of the present application, the negative electrode active material layer may optionally further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0099] According to an embodiment of the present application, a negative electrode sheet can be prepared in the following manner: the components for preparing a negative electrode sheet (such as a negative electrode active material, a conductive agent, a binder and any other components) are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing and other processes, a negative electrode sheet can be obtained.

[0100] The present invention has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0101] According to an embodiment of the present application, the battery may include an outer package for packaging the positive electrode sheet, the negative electrode sheet and the electrolyte.

[0102] According to an embodiment of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0103] According to an embodiment of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0104] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0105] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0106] The fifth aspect of the present invention provides an electric device. According to an embodiment of the present application, the electric device includes the battery of the fourth aspect. Therefore, the electric device of the present application has high-efficiency energy output and excellent service life and safety performance.

[0107] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0108] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0109] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0110] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0111] It should be noted that the features and advantages described above for the positive electrode plate of the third aspect of the present application are also applicable to the battery of the fourth aspect and the electrical device of the fifth aspect of the present application, and will not be repeated here.

[0112] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0113] Example 1

[0114] 1. Lithium supplement Li5FeO4(D 50 value is 10μm), electronic conductor aluminum-doped zinc oxide (AZO, aluminum doping ratio is 2%, D 50 5nm) and fast ion conductor lithium aluminum titanium phosphate (Nasicon structure, LATP, D 50 The total mass ratio of Li5FeO4, AZO and LATP to NMP is 1:1.

[0115] 2. The mixed liquid was sent to a spray dryer for spray drying under argon protection, with a pressure of 0.5 MPa, an inlet temperature of 200°C, an outlet temperature of 90°C, and a feed rate of 1 L / h to obtain a solid powder.

[0116] 3. After spray drying, sinter the solid powder under argon protection at a temperature of 300°C for 1.5 hours. After sintering, sieve to obtain the positive electrode lithium supplement material.

[0117] 4. Expose the positive electrode lithium replenishing material to air at a temperature of 25° C. and a humidity of 40% for 24 hours to obtain the corresponding positive electrode lithium replenishing material after placement.

[0118] 5. The positive electrode lithium replenishing material of step 3 and the positive electrode lithium replenishing material after placement of step 4 are respectively used as positive electrode materials to make button batteries, wherein the battery made of the positive electrode lithium replenishing material without placement is recorded as battery 1, and the battery made of the positive electrode lithium replenishing material after placement is recorded as battery 2. The specific production method is as follows:

[0119] The positive electrode lithium supplement material, conductive carbon black, and PVDF are dispersed in NMP at a mass ratio of 8:1:1, and the positive electrode sheet is obtained by slurry mixing, coating, drying, and rolling. A metal lithium sheet is used as the negative electrode sheet, a Celgard2400 polypropylene film is used as a separator, and a mixed solution of EC and DMC containing 1 mol / L lithium hexafluorophosphate (volume ratio of 1:1) is used as an electrolyte. The battery is assembled with the above-mentioned positive electrode sheet in a glove box filled with argon, and then a lithium-ion battery is obtained through the steps of standing, pressurized formation, aging, exhaust, and capacity separation.

[0120] Example 2-23

[0121] The differences between Examples 2-23 and Example 1 are shown in Table 1.

[0122] Comparative Example 1

[0123] Uncoated and modified positive electrode lithium replenishing material Li5FeO4.

[0124] Comparative Example 2

[0125] The difference between Comparative Example 2 and Example 1 is that step 1 does not contain a fast ion conductor.

[0126] Comparative Example 3

[0127] The difference between Comparative Example 3 and Example 1 is that step 1 does not contain an electronic conductor.

[0128] Comparative Example 4

[0129] The difference between Comparative Example 4 and Example 1 is that the electronic conductor aluminum-doped zinc oxide (AZO) is replaced by the electronic inert body aluminum oxide.

[0130] Comparative Example 5

[0131] 1. Combine Ketjen Black (carbon material, average particle size 30 μm) and fast ion conductor material LATP (D 50The particle size is 100nm) and Li5FeO4 are weighed according to a certain ratio, wherein the mass ratio of Ketjen black: LATP is 20:80, and the mass ratio of (Ketjen black + LATP): Li5FeO4 is 1.5:100, and then low-speed ball milling is performed for 30min at a speed of 500rpm under argon protection to form a coating layer.

[0132] 2. The coated and modified material is dried at 300°C for 4 hours to obtain a positive electrode lithium replenishing material.

[0133] Test Case

[0134] The performance of the batteries prepared in Examples 1 to 23 and Comparative Examples 1 to 5 were tested respectively, and the specific methods are as follows:

[0135] The LAND battery test system was used to charge the battery at a constant current of 0.066C. The charging cut-off voltages of Li5FeO4, Li2NiO2 and Li6CoO4 were 4.2V, 4.5V and 4.2V respectively. The first charging specific capacity of the battery was recorded. The test results are shown in Table 1.

[0136] It can be seen from Table 1 that compared with Comparative Examples 1 to 5, the first charge specific capacity of the batteries prepared in Examples 1 to 23 and the first charge specific capacity after being placed in the air at room temperature for 24 hours are both higher, indicating that the coating and modification of the Li5FeO4 material with a fast ion conductor and an electronic conductor can effectively improve its electronic conduction and ion conduction capabilities, improve the decomposition efficiency of the positive electrode lithium supplement material, and enhance the lithium supplement effect. Moreover, compared with Comparative Example 2 which only uses an electronic conductor or Comparative Example 3 which only uses a fast ion conductor, Example 1 uses a fast ion conductor and an electronic conductor for co-coating, which can provide more grain boundaries, thereby increasing the lithium ion transmission path and promoting the rapid migration of lithium ions. This structure not only improves the interfacial reaction kinetics, but also helps to achieve a more uniform charge distribution and more efficient ion transmission, improve the decomposition efficiency of the positive electrode lithium supplement material, and enhance the lithium supplement effect. In addition, the first charge specific capacity of the batteries prepared before and after the positive electrode lithium supplement material of Examples 1 to 23 is close, indicating that the interface stability of the Li5FeO4 material is improved after the coating and modification, reducing its reaction with H2O and CO2 in the air, and improving Li x M y O z Decomposition efficiency.

[0137] It can be seen from Examples 1, 18 and 21 that the particles of the electron conductor or fast ion conductor are too large, the coating uniformity is slightly low, and an island structure may be formed, which is not easy to effectively coat the lithium supplement agent, the lithium supplement effect is slightly low, and there are more side reactions. In addition, the interface stability of the Li5FeO4 material is reduced, so that the first charge specific capacity of the battery made before and after the positive electrode lithium supplement material is placed changes greatly.

[0138] It can be seen from Examples 1, 19 and 20 that the D 50 If the ratio of the value is too high or too low, the coating uniformity will be reduced, it will be difficult to effectively coat the lithium supplement agent, the lithium supplement effect will be slightly lower, and there will be more side reactions. In addition, the interface stability of the Li5FeO4 material is reduced, which makes the first charge specific capacity of the battery made before and after the positive electrode lithium supplement material is placed change greatly.

[0139] It can be seen from Example 1 and Example 22 that the mass ratio of the fast ion conductor to the electronic conductor in the coating layer is low, that is, the content of the electronic conductor is high, which will reduce the lithium ion transmission performance, increase the interface impedance, and make it difficult for the lithium supplement agent to quickly de-lithium, affecting the lithium supplement effect, resulting in a low charge specific capacity. In addition, the interface stability of the Li5FeO4 material is reduced, resulting in a large change in the first charge specific capacity of the battery made before and after the positive electrode lithium supplement material is placed.

[0140] It can be seen from Example 1 and Example 23 that the mass ratio of the core to the coating layer is low, that is, the coating layer is too much, which will increase the interface impedance, make it difficult for the lithium supplement agent to quickly remove lithium, affect the lithium supplement effect, and lead to a low charge capacity. In addition, the interface stability of the Li5FeO4 material is reduced, so that the first charge capacity of the battery made before and after the positive electrode lithium supplement material is placed changes greatly.

[0141]

[0142]

[0143]

[0144] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A positive electrode lithium supplement material, characterized in that: include: The core includes a lithium supplement, and the lithium supplement includes Li x M y O z , M includes at least one of Fe, Co and Ni, 1≤x≤6, 1≤y≤6, 1≤z≤6; A coating layer, the coating layer covers at least a portion of the surface of the core, and the coating layer includes a fast ion conductor and an electron conductor; The electronic conductor includes at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride, niobium nitride and indium nitride.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: The fast ion conductor comprises at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium cobalt oxide, lithium niobate and lithium nickel manganese oxide.

3. The positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The fast ion conductor comprises: at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium cobalt oxide and lithium niobate; And / or, the electronic conductor includes: at least one of aluminum-doped zinc oxide, antimony-doped tin dioxide, indium tin oxide, aluminum nitride, titanium nitride, gallium nitride and indium nitride.

4. The positive electrode lithium supplement material according to claim 1, characterized in that: The D of the fast ion conductor 50 The particle size is larger than the D 50 Particle size.

5. The positive electrode lithium supplement material according to claim 1 or 4, characterized in that: The electron conductor D 50 Particle size is 1nm~20nm; and / or, the fast ion conductor has a D 50 The particle size is 50nm~200nm.

6. The positive electrode lithium supplement material according to any one of claims 1 to 5, characterized in that: The D of the fast ion conductor 50 Particle size and the D of the electronic conductor 50 The particle size ratio is (2~100):

1.

7. The positive electrode lithium supplement material according to any one of claims 1 to 6, characterized in that: The Li x M y O z D 50 The particle size is larger than the D 50 Particle size.

8. The positive electrode lithium supplement material according to any one of claims 1 to 7, characterized in that: The Li x M y O z D 50 The particle size is 1μm~20μm.

9. The positive electrode lithium supplement material according to any one of claims 1 to 8, characterized in that: The mass ratio of the core to the coating is 100:(0.1-10); And / or, the mass ratio of the fast ion conductor to the electronic conductor is (50-99.9):(0.1-50).

10. The positive electrode lithium supplement material according to claim 1, characterized in that: The lithium supplement includes Li5FeO4, Li6CoO4 or Li2NiO2.

11. A method for preparing the positive electrode lithium supplement material according to any one of claims 1 to 10, characterized in that: include: The fast ion conductor and the electronic conductor are coated on at least a portion of the surface of the lithium supplement agent to form a coating layer, thereby obtaining the positive electrode lithium supplement material.

12. The method according to claim 11, characterized in that include: The fast ion conductor, the electronic conductor, the lithium supplement agent and an organic solvent are mixed to obtain a mixed solution; The mixed solution is spray-dried to obtain a solid powder; The solid powder is sintered to obtain the positive electrode lithium supplement material.

13. The method according to claim 12, characterized in that The mass ratio of the total mass of the fast ion conductor, the electronic conductor and the lithium supplement agent to the mass ratio of the organic solvent is 1:(0.8-1.2); And / or, the spray drying process satisfies at least one of the following conditions: The pressure is 0.2MPa~1MPa; Inlet air temperature is 100℃~300℃; The outlet temperature is 80℃~100℃; Feed rate is 0.5L / h~2L / h; And / or, the sintering treatment temperature is 200° C. to 400° C., and the time is 1 hour to 2 hours.

14. A positive electrode sheet, characterized in that: The invention comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing material comprises the positive electrode lithium replenishing material according to any one of claims 1 to 10 or the positive electrode lithium replenishing material obtained by the method for preparing the positive electrode lithium replenishing material according to any one of claims 11 to 13.

15. The positive electrode sheet according to claim 14, characterized in that: The mass fraction of the positive electrode lithium supplement material in the positive electrode active material layer is 0.05% to 5%.

16. A battery, characterized in that: Including the positive electrode sheet as described in claim 14 or 15.

17. An electrical device, characterized in that: Comprising the battery of claim 16.

Citation Information

Patent Citations

  • Lithium supplementing material and positive electrode including same

    CN110867584A

  • Positive electrode material, secondary battery and electric equipment

    CN116364891A

  • Lithium supplement composite material and preparation method and application thereof

    CN117559013A

  • Composite lithium supplementing material and preparation method thereof, positive pole piece and secondary battery

    CN117878448A

  • Positive electrode lithium supplementing material and preparation method thereof, positive electrode, battery and electric equipment

    CN118610460A